Asset Management Contributes to Optimizing a Distribution System. Issue 9 (1st September 2014) - Martin, Barb
Abstract : The asset management planning process lets a water utility derive maximum value from its physical assets. Regardless of its size, a utility can reap huge benefits from a comprehensive asset management program.